KOMPOSISI MUSIK “FANTASY OF THE DREAM” - Ilham Yogi Saputra; Jagar Lumban Toruan; Yensharti Yensharti (SENDRATASIK UNP, 2013)
Abstract Music Composition "The Dream" is a music composition that the making is departed from an imagination laid out with the kind of Chamber Music by presenting new colorsin the composition of the creation, which form a complete work of music. This type of art work bases the music groove on the conventional true events and emphasizes the supportive atmosphere in the composition. The Dream musical composition consists of 4 main forms using tempo Grave, Adante, moderatoassai, and moderato, which can describe the atmosphere tha tis present in a dream. The dream thatcomes up is intrepeted by the autho as an outline view of reality that appears to the mind of a writer like remorse, emotion, uncertainty, sincerity and dreams. The presentation of music composition "The Dream" puts some basic instruments and supporting instruments with piano as the main melody, group of strings (Violin, Viola, Cello), saluang sirompak, saluang darek, and keyboard as accompainement in music composition encapsulated by the author in the concept of this show.   Kata kunci: Komposisi, Musik, Fantasy of The dream